2013
DOI: 10.1177/1367493513510630
|View full text |Cite
|
Sign up to set email alerts
|

‘Why does it happen like this?’ Consulting with users and providers prior to an evaluation of services for children with life limiting conditions and their families

Abstract: Children with life limiting conditions and their families have complex needs. Evaluations must consider their views and perspectives to ensure care is relevant, appropriate and acceptable. We consulted with children, young people, their parents and local professionals to gain a more informed picture of issues affecting them prior to preparing a bid to evaluate services in the area. Multiple methods included focus groups, face-to-face and telephone interviews and participatory activities. Recordings and product… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
34
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(34 citation statements)
references
References 39 publications
(42 reference statements)
0
34
0
Order By: Relevance
“…The importance of assessing children within the context of the family has however been highlighted in the international literature (Friebert & Huff, 2009;Hunt et al, 2013). Sloper and Beresford (2006) found that, although needs were often recognised by service providers, they were often unmet.…”
Section: Context Of Paediatric Palliative Carementioning
confidence: 99%
See 3 more Smart Citations
“…The importance of assessing children within the context of the family has however been highlighted in the international literature (Friebert & Huff, 2009;Hunt et al, 2013). Sloper and Beresford (2006) found that, although needs were often recognised by service providers, they were often unmet.…”
Section: Context Of Paediatric Palliative Carementioning
confidence: 99%
“…Strand 5. To facilitate involvement of parents, carers and young people in underpinning, advising and supporting the research Ensuring that the family is at the centre of care demands that all those involved in supporting the child or young person and the family work with, and on their behalf (Hunt et al, 2013). Professional carers are likely to come from a wide range of services and each will have their preferred way of working, organisational structures, salary scales and professional development programmes (Jassal & Sims, 2006).…”
Section: Context Of Paediatric Palliative Carementioning
confidence: 99%
See 2 more Smart Citations
“…The scoping review identification process highlighted 48 studies which discussed the unmet needs of children with LLCs and their families from the parent’s perspective 15 27–73. The references of these 48 studies were then hand-searched by GC, identifying seven further studies meeting the inclusion criteria 74–80.…”
Section: Resultsmentioning
confidence: 99%